Provincial-Level Dynamic Modeling of Climate Influence on Agriculture and Consumption: Case Studies in Central Java, East Java, Bali, and North Sumatra - Ariyani Wardhana; Ruci Meiyanti; Handy Noviyarto; Kelik Budiana (Universitas Negeri Semarang, 2026)
Indonesia’s agricultural sector is increasingly exposed to climate change, as shifts in rainfall, temperature, and humidity disrupt crop yields and farmer livelihoods. These disruptions weaken domestic supply and heighten reliance on external sources. To capture regional differences, this study examines East Java, Central Java, Bali, and North Sumatra, using a Power BI-based interactive dashboard to integrate climate indicators, production data, commodity prices, and consumption patterns from 2018 to 2021. The results highlight distinct provincial dynamics. In Bali, yields respond positively to humidity but decline with rainfall, while Central Java’s rice production is strongly shaped by rainfall variability. East Java’s horticultural crops are highly sensitive to humidity and temperature, and North Sumatra’s diversified systems show inverse effects from all three climate variables. Correlation analyses suggest that higher harvest yields slightly reduce commodity prices, particularly for rice, shallots, and garlic; the coefficients remain weak (–0.1 to –0.4), reflecting the role of transportation, market access, and trade pressures. By visualizing these relationships, the dashboard underscores interconnected vulnerabilities such as dependence on staple crops, reliance on imports, and affordability challenges. It also provides policymakers with a practical tool to monitor climate-related risks and price instability. Overall, the findings emphasize the need for integrated food security policies that combine climate science, crop management, and economic equity to support sustainable outcomes across Indonesia.